Non-peptidic substrate-mimetic inhibitors of Akt as potential anti-cancer agents. - Kayser-Bricker, K; Glenn, M; Lee, S; Sebti, S; Cheng, J; Hamilton, A (2009)
Akt has emerged as a critical target for the development of anti-cancer therapies. It has been found to be amplified, overexpressed, or constitutively activated in numerous human malignancies with oncogenesis derived from the simultaneous promotion of cell survival and suppression of apoptosis. A valuable alternative to the more common ATP-mimetic based chemotherapies is a substrate-mimetic approach, which has the potential advantage of inherent specificity of the substrate-binding pocket. In this paper we present the development of high affinity non-peptidic, substrate-mimetic inhibitors based on the minimum GSK3beta substrate sequence. Optimization of initial peptidic leads resulted in the development of several classes of small molecule inhibitors, which have comparable potency to the initial peptidomimetics, while eliminating the remaining amino acid residues. We have identified the first non-peptidic substrate-mimetic lead inhibitors of Akt 29a-b, which have affinities of 17 and 12 microM, respectively. This strategy has potential to provide a useful set of molecular probes to assist in the validation of Akt as a potential target for anti-cancer drug design.